Palladium (0) catalyzed synthesis of thiophene based 1,3,4-oxadiazoles their reactivities and potential nonlinear optical properties - Abbas, Mujahad, Abbas; Komal, Rizwan; Nasir, Rasool; Muhammad Ali, Hashmi; Gulraiz, Ahmad; Umer, Rashid (Chiang Mai University, 2020)
Novel thiophene based 1,3,4-oxadiazoles were synthesized via Suzuki cross-coupling of 2-(5-bromothiphen-2-yl)-5-phenyl-1,3,4-oxadiazole with various substituted aryl-boronic acids in significant yields (58-78%). Density functional theory (DFT) investigations were accomplised on novel oxadiazoles (5a-5j) to explore their structural properties. Reactivity-descriptors and frontier molecular orbitals (FMOs) studies were carried out by using PBE0-D3BJ/def2-TZVP level of theory to determine structural properties, reactivity and reacting sites of synthesized molecules (5a-5j).